(untitled) (Al-Academy, 2025)
This study aims to explore and analyze the political, social, and culture symbolism embedded in printmaking works produced in the Kingdom of Saudi Arabia between 2000 an 2024- a period characterized by profound transformations across the social, cultural, and political spheres. Using a critical visual analysis methodology, the research focuses on a selection of printmaking: Neal Mulla, Fayez Abu Haris, and Sami Al-Bar. The study examines hand-prouced prints using intaglio, woodcut, and linocut techniques, highlighting themes of social transformation, moderation, an belonging within an evolving visual context